Christus medicus: teologia i metàfora de la curació espiritual. - Navarro, Anna Isabel Peirats (Zeitschrift für Katalanistik, 2022)
This article focuses on the study of the topic of Christus medicus from a theological and literary point of view in late medieval texts. It is necessary to start from the fact that this motif is not easily found in original texts, nor in the Holy Scriptures, with the same relief in which it operates in the discourses of the preachers and in literary works of the 14th and 15th centuries. The presence of the topic can take shape in three areas: recurring similarities between medical and religious terms; signs of Christ as the healer of the people, thaumaturge, and metaphorical aspect, according to which Christ is the true physician. This image becomes a leitmotif, and gives cohesion to various fragments of sermons both by Giordano Da Pisa and by St. Vincent Ferrer delivered in Europe, with success among the public who listened to them. In addition, in Jaume Roig's Spill it is shown that authentic health requires true, divine medicine. This article will discuss how this motif acquires a very new and recurring tone in many passages of the Vita Christi of Isabel de Villena, as part of the goal of following the model of Christ and the Virgin, as a spiritual doctor of humanity, through meditation and reflection.